Stress Redistribution Explains Anti-correlated Subglacial Pressure Variations - Lefeuvre, Pierre-Marie; Zwinger, Thomas; Jackson, Miriam; Gagliardini, Olivier; Lappegard, Gaute; Hagen, Jon Ove (Frontiers in Earth Science, 2018)
We used a finite element model to interpret anti-correlated pressure variations at the base of a glacier to show the importance of stress redistribution in the basal ice. Two pairs of load cells are installed 20 m apart at the base of the 210 m thick Engabreen glacier in Northern Norway. Pressurisation of a subglacial channel located over one pair led to anti-correlation in pressure between them. A full Stokes 3D model of a 210 m thick and 25-200 m wide glacier with a pressurised subglacial channel represented as a pressure boundary condition was used to investigate the anti-correlated response at the bed. The model reproduced the anti-correlated pressure response at the glacier bed and variations in pressure of the same order of magnitude as the load cell observations. The anti-correlation pattern was shown to depend on the bed/surface slope such that the anti-correlated pressure variations were reproduced at a distance greater than 10-20 m from the channel when the bed slope was zero, whereas anti-correlation occurred within 10 m of the channel when the bed was inclined by 5 degrees. Pressurisation of the channel led to lateral or vertical ice flow away from the channel, support of the overlying ice and reduction of the normal stress on the bed. If the modelled cross-section was laterally constrained and the bed flat, the resulting bridging effect diverted some of the normal forces acting on the bed to the sides. In contrast, if the bed was inclined, then channel support was vertical only. The model showed that the effect of stress redistribution depends on the slope as well as the geometry of the subglacial channel and glacier, and can lead to an opposite response in pressure at the same distance from the channel.